PENINGKATAN KUALITAS PEMBELAJARAN KULIAH LAPANGAN GEOLOGI PADA MAHASISWA GEOGRAFI FKIP UNDANA MELALUI LESSON STUDY - Muhammad Husain Hasan (Universitas Negeri Gorontalo, 2021)
Geology is one of subject course in Geography Study which requires field studiy. Field studies that have been carried out so far are considered less effective because it has weaknesses from various aspects. The research method used was a descriptive survey. Data collection techniques by observation and interviews. The results showed that the geology topic field lecture activity at the first location was not optimal with a mean score of 80 pre-field observations, 60 on field activities, and 65 on activity reporting followed by learning reflections. Geological field course activities at the second location showed improvements where the results of the reflections at the first location were used to improve the quality at the second location so that observations were obtained with an average score of 80 in the pre-field, 77 in field activities, and 75 in activity reporting